Transformative Potential of Induced Pluripotent Stem Cells in Congenital Heart Disease Research and Treatment - Mohammed A. Mashali; Isabelle Deschênes; Nancy S. Saad (Children)
Congenital heart disease (CHD), the most common congenital anomaly, remains a significant lifelong burden despite advancements in medical and surgical interventions. Induced pluripotent stem cells (iPSCs) have emerged as a groundbreaking platform in CHD research, offering patient-specific models to investigate the genetic, epigenetic, and molecular mechanisms driving the disease. Utilizing technologies such as CRISPR/Cas9 gene editing, cardiac organoids, and high-throughput screening, iPSCs enable innovative strategies in disease modeling, precision drug discovery, and regenerative therapies. However, clinical translation faces challenges related to immaturity, differentiation variability, large-scale feasibility, and tumorigenicity. Addressing these barriers will require standardized protocols, bioengineering solutions, and interdisciplinary collaboration. This review examines the critical role of iPSCs in advancing CHD research and care, demonstrating their potential to revolutionize treatment through patient-specific, regenerative approaches. By addressing current limitations and advancing iPSC technology, the field is positioned to pave the way for precision-based CHD therapies for this lifelong condition.